INVESTIGATING EFL VOCATIONAL HIGH SCHOOL STUDENTS’ SPEAKING PERCEPTION THROUGH INSTAGRAM VLOG - Yoannes Yuka Krisdianata; Ouda Teda Ena (Journal of English Educational Study (JEES), 2022)
The growth of technology in industry 4.0 was really fast and unimagined. The development also happened in the education field. The use of technology was helping teachers and students to develop their competencies. This study was conducted to investigate vocational high school students’ views of speaking through the use of Instagram vlogs in English courses. Thirty-two students’ perceptions toward the use of Instagram vlogs in learning English speaking skills were studied. The result was presented in the form of descriptive analysis using the mean and percentages. Moreover, there were three open-ended questions to give further information on students’ perspectives on learning English speaking skills through Instagram vlogs. The result indicated that Instagram vlog helped students to learn English better, improve their vocabulary, and widen their knowledge.